1991
DOI: 10.1073/pnas.88.15.6427
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the tetraploid intermediate is associated with the development of cells with more than four centrioles in the elastase-simian virus 40 tumor antigen transgenic mouse model of pancreatic cancer.

Abstract: The development of pancreatic cancer in transgenic mice expressing the simian virus 40 tumor antigen placed under controlling regions of the elastase I gene is characterized by the sequential appearance of tetraploid and then multiple aneuploid cell populations. Pancreatic tissues from such transgenic mice were studied between 8 and 32 days of age. Virtually 100% of acinar cell nuclei had immunohistochemically detectable tumor antigen by 18 days. Tetraploid cells were demonstrated by DNA content flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 31 publications
4
67
0
1
Order By: Relevance
“…Other reports also support the idea that mutations in mitotic checkpoint proteins can cause genomic instability and in rare cases give rise to cancer (36,39). Because tetraploidy is frequently an intermediate step for progression to aneuploidy, it is particularly interesting that T antigen has already been shown to induce tetraploid DNA content in both permissive and nonpermissive cells (37,40). We found that Parental U2OS or U2OS lines stably expressing T antigen or the dl89 -97 mutant were treated with nocodazole for 48 h, and the extent of endoreduplication was determined by fluorescence-activated cell sorting analysis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Other reports also support the idea that mutations in mitotic checkpoint proteins can cause genomic instability and in rare cases give rise to cancer (36,39). Because tetraploidy is frequently an intermediate step for progression to aneuploidy, it is particularly interesting that T antigen has already been shown to induce tetraploid DNA content in both permissive and nonpermissive cells (37,40). We found that Parental U2OS or U2OS lines stably expressing T antigen or the dl89 -97 mutant were treated with nocodazole for 48 h, and the extent of endoreduplication was determined by fluorescence-activated cell sorting analysis.…”
Section: Discussionmentioning
confidence: 75%
“…The interaction of Bub1 and T antigen may explain several previous reports that demonstrated that T antigen is able to induce aneuploidy and genetic instability, giving rise to both structural and numerical chromosome aberrations (14)(15)(16)(17)37). It had been proposed that this instability was most likely caused by the ability of T antigen to interact with and inactivate the p53 protein.…”
Section: Discussionmentioning
confidence: 84%
“…In 1991 Levine et al reported that formation of tetraploid intermediates is associated with the development of cells with more than four centrioles in the development of pancreatic cancer in transgenic mice expressing the simian virus 40 tumor antigen (30), which is one of the viral oncoproteins known to interact with p53 (31). Furthermore, Levine et al observed that in ulcerative colitis with dysplasia or cancer genomic instability and clonal evolution of aneuploid cells were associated with malignancy progression (32).…”
Section: Discussionmentioning
confidence: 99%
“…Increased G2/M DNA content has been previously described in pancreatic cancer models. For example, pancreatic tumors develop in transgenic mice expressing the SV40 Tantigen under the control of the elastase I promoter (Levine et al, 1991). In these animals, the 4N state is associated with increased number of centrioles per cell.…”
Section: Agn193198 -An Effective Inhibitor Of Pancreatic Cell Prolifementioning
confidence: 99%